2020
DOI: 10.1177/0194599820935850
|View full text |Cite
|
Sign up to set email alerts
|

A Second Pandemic? Perspective on Information Overload in the COVID‐19 Era

Abstract: The outbreak of COVID-19 has affected the globe in previously unimaginable ways, with far-reaching economic and social implications. It has also led to an outpouring of daily, ever-changing information. To assess the amount of data that were emerging, a PubMed search related to COVID-19 was performed. Nearly 8000 articles have been published since the virus was defined 4 months ago. This number has grown exponentially every month, potentially hindering our ability to discern what is scientifically important. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 1 publication
1
29
0
Order By: Relevance
“…Among Americans, 72% report using an online news source for COVID-19 information in the last week, with 47% reporting that the source was social media [ 3 ]. The number of research articles focusing on COVID-19 has also grown exponentially; more research articles about the disease were published in the first 4 months of the COVID-19 pandemic than throughout the entirety of the severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS) pandemics combined [ 4 ]. Unfortunately, this breadth, and the speed with which information can travel, sets the stage for the rapid transmission of misinformation, conspiracy theories, and fake news about the pandemic [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among Americans, 72% report using an online news source for COVID-19 information in the last week, with 47% reporting that the source was social media [ 3 ]. The number of research articles focusing on COVID-19 has also grown exponentially; more research articles about the disease were published in the first 4 months of the COVID-19 pandemic than throughout the entirety of the severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS) pandemics combined [ 4 ]. Unfortunately, this breadth, and the speed with which information can travel, sets the stage for the rapid transmission of misinformation, conspiracy theories, and fake news about the pandemic [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…For that reason, COVID-19 information overload (COVIO) has received much attention from researchers around the world (Mohammed et al, 2021;Valika et al, 2020). COVIO is the information overload caused by the pandemic.…”
Section: Sayeed Al-zamanmentioning
confidence: 99%
“…Studies found that even COVID-19 related scholarly outputs can produce information overload. For example, 10,055 papers were published on COVID-19 during the first three months of the outbreak and this number was growing rapidly, potentially hindering the public's understanding of the pandemic scientifically (Valika et al, 2020).…”
Section: Sayeed Al-zamanmentioning
confidence: 99%
“…In light of this ongoing pandemic, it is crucial to investigate the impact of a complete switch to e-Learning systems on students' perception of information. Recent studies on information overload during the pandemic state show that information production exceeded all previous pandemics due to the ease of accessing, creating, and sharing information (Valika et al, 2020). The association of this over-abundance of information has been shown to reduce wellbeing, as Fan and Smith (2021) (in press) demonstrated in their study on Chinese adults.…”
Section: Information Overloadmentioning
confidence: 99%